Pengaruh Experiential Marketing dan Desain Produk terhadap Kepuasan Konsumen dengan Keputusan Pembelian sebagai Variabel Intervening pada Konsumen Smartphone Xiaomi di Yogyakarta - Farhan Falah; Henny Welsa; Putri Dwi Cahyani (Universitas Batanghari, 2023)
Advances in technology and information are currently experiencing very fast growth, one of which is telecommunication, where almost every individual needs it in their daily activities. Because of necessity, technology continues to be developed so that it can do many things that are usually done by computers. Smartphones are now the most important part of your routine. The rise of smartphone use in modern society's lifestyle has resulted in the number of individuals using smartphones continuing to increase from one year to the next. This has become a trigger for companies to aggressively conduct research and sales to Indonesia, one of which is the Xiaomi smartphone company by creating smartphones that are supported by the latest capabilities and attractive designs. Even though Xiaomi smartphones are in great demand by the Indonesian people, even though they are not yet the market leaders because each individual has different tastes, needs and desires in determining the smartphone they will use to get certain satisfaction. So the purpose of this study was to analyze the influence of experiential marketing and product design on consumer satisfaction with purchase decisions as an intervening variable for Xiaomi consumers. This research is a quantitative study by distributing questionnaires to a random sample of 100 respondents living in Yogyakarta. This study uses the category of non-probability sampling with accidental purposive sampling technique. From this study, it was found that all variables had a positive influence and Experiential Marketing (EM) on Consumer Satisfaction (KK) with Purchase Decision (KP) as an acceptable intervening variable. Product Design (DP) on Consumer Satisfaction (KK) with Purchasing Decision (KP) as the intervening variable is accepted.